Brill's companion to the reception of Aeschylus - Kennedy, Rebecca Futo, 1974- (Brill's Companions to Classical Reception, 2017)
Brill's Companion to the Reception of Aeschylus explores the various ways Aeschylus' tragedies have been discussed, parodied, translated, revisioned, adapted, and integrated into other works over the course of the last 2500 years. Immensely popular while alive, Aeschylus' reception begins in his own lifetime. And, while he has not been the most reproduced of the three Attic tragedians on the stage since then, his receptions have transcended genre and crossed to nearly every continent. While still engaging with Aeschylus' theatrical reception, the volume also explores Aeschylus off the stage--in radio, the classroom, television, political theory, philosophy, science fiction and beyond.